2011
DOI: 10.3989/scimar.03601.15c
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of protection from harvesting in populations of two limpet species in a recently established marine protected area

Abstract: SUMMARY: This study aimed to evaluate the effects of protection from extractive activities on the population structure of two limpets of commercial interest, Patella ulyssiponensis and Patella candei crenata. We evaluated the status of these populations in La Palma Marine Protected Area (MPA), Canary Islands, and in comparable unprotected areas in the lower intertidal zone of the same island. We showed that the density of P. ulyssiponensis depended greatly on the level of protection, whereas the effects of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…The observed recovery pattern in the exploited populations of both limpets agreed with Martins (2009) that observed the same correlation between limpets' abundances and the proximity to coastal settlements in Azores (NE Atlantic). Also, when considering the control sites, these results are concurrent with López et al (2012) that observed that sites where harvesting is not allowed, e.g. marine protected areas (MPAs), assemblages had larger individuals and higher abundances, and also an increase of their populations was observed.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The observed recovery pattern in the exploited populations of both limpets agreed with Martins (2009) that observed the same correlation between limpets' abundances and the proximity to coastal settlements in Azores (NE Atlantic). Also, when considering the control sites, these results are concurrent with López et al (2012) that observed that sites where harvesting is not allowed, e.g. marine protected areas (MPAs), assemblages had larger individuals and higher abundances, and also an increase of their populations was observed.…”
Section: Discussionsupporting
confidence: 81%
“…The loss of large individuals produces cascading effects on the biology of limpets in exploited populations, including changes in lifehistory parameters, demographics, reproductive success, genetics, as well as changes in ecological interactions and limpet behaviour (Fenberg and Roy, 2008;Espinosa et al, 2009;López et al, 2012;Henriques et al, 2017). In the most extreme cases, harvesting pressure is recognized to have led to the high fragmentation of limpet assemblages as occurred for P. candei crenata and P. aspera in the Canaries (Riera et al, 2016) and even to the disappearance of populations of P. ferruginea, an endemic and endangered species from the Mediterranean Sea (Espinosa, 2009), and of the endemic species Cellana sandwicensis (Pease, 1861), Cellana exarata (Reeve, 1854) and Cellana talcosa (Gould, 1846) in Hawaii (Valledor, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Legislation does not differ much among regions, with the establishment of limpet no‐take areas, minimum legal catch sizes, and seasonal fishing closures. Unfortunately, these actions have been largely ineffective in protecting such resource (Diogo, Pereira, & Schmiing, ; López et al., ; Martins et al., ; Riera et al., ), mostly because of illegal harvesting and lack of or insufficient enforcement. Protective measures need to be adjusted to the particular life‐history traits of P. candei in each archipelago (e.g., temporal variation in reproduction, recruitment, population dynamics).…”
Section: Discussionmentioning
confidence: 99%
“…Kido & Murray, 2003;Branch & Odendaal, 2003;Martins et al, 2011;López et al, 2012). Highly vulnerable species are more likely to benefit from the establishment of protected areas, as demonstrated by case studies on large limpets that are often present within MPAs and other protected areas (Fenberg & Roy, 2012;Espinosa et al, 2014;García-Gómez et al, 2015).…”
Section: The Role Of the Mpa And Of Physical Accessibilitymentioning
confidence: 82%